Memory retrieval brain–behavior disconnection in mild traumatic brain injury: A magnetoencephalography and diffusion tensor imaging study. Issue 17 (7th July 2022) - Hung, Yuwen; Vandewouw, Marlee; Emami, Zahra; Bells, Sonya; Rudberg, Nicole; da Costa, Leodante; Dunkley, Benjamin T.
Abstract: Mild traumatic brain (mTBI) injury is often associated with long‐term cognitive and behavioral complications, including an increased risk of memory impairment. Current research challenges include a lack of cross‐modal convergence regarding the underlying neural–behavioral mechanisms of mTBI, which hinders therapeutics and outcome management for this frequently under‐treated and vulnerable population. We used multi‐modality imaging methods including magnetoencephalography (MEG) and diffusion tensor imaging (DTI) to investigate brain–behavior impairment in mTBI related to working memory. A total of 41 participants were recruited, including 23 patients with a first‐time mTBI imaged within 3 months of injury (all male, age = 29.9, SD = 6.9), and 18 control participants (all male, age = 27.3, SD = 5.3). Whole‐brain statistics revealed spatially concomitant functional–structural disruptions in brain–behavior interactions in working memory in the mTBI group compared with the control group. These disruptions are located in the hippocampal–prefrontal region and, additionally, in the amygdala (measured by MEG neural activation and DTI measures of fractional anisotropy in relation to working memory performance; p < .05, two‐way ANCOVA, nonparametric permutations, corrected). Impaired brain–behavior connections found in the hippocampal–prefrontal and amygdala circuits indicate brain dysregulation of memory, which may leave mTBI patients vulnerable to increased environmental demands exerting memory resources, leading to related cognitive and emotional psychopathologies. The findings yield clinical implications and highlight a need for early rehabilitation after mTBI, including attention‐ and sensory‐based behavioral exercises. Abstract : Question : We ask whether mild traumatic brain injury (mTBI) impairs the two‐dimensional, brain–behavior regulatory capacity, by using multi‐modality neuroimaging methods including magnetoencephalography (MEG) and diffusion tensor imaging (DTI). Findings : Whole‐brain analyses revealed converging functional–structural evidence in that mTBI patients showed impaired brain–behavior regulation of working memory, compared with the healthy controls, located in the hippocampal–prefrontal and amygdala regions. Meaning : Findings provide robust and reliable evidence underlying memory systems vulnerability in mTBI: Impaired brain–behavior regulation in the limbic–prefrontal circuits represents brain disorganization, which may leave mTBI patients vulnerable and at increased risk for memory‐related psychopathologies.